Comprehensiveness of punishment for baby dumping: definition, severity and coverage - Termizi, Mazbah; Abdullah, Nurhidayah; Mohd Jaafar, Noor Ismawati (2014)
The act of abandoning or disposing foetus and newborn is widely known as baby dumping in Malaysia. Even though the statistics of the crime is difficult to obtain and mostly underreported, the issue has attracted much attention and being considered by the society in most part of the world as a heartless crime. The offender could be charged under relevant act which enforcing stipulated punishment. Using content analysis, the paper explores the punishment methods available for those convicted to the crime in Malaysia and few selected countries. The types of punishment with its guarded act or statute are identified and then comparison of its severity is done. The paper argues that the severity of the punishment might have positive impact on reducing the crime. The differences in definition and coverage are also discussed in order to determine the comprehensiveness of punishment methods among the selected countries of study.